Westerdykella reniformis sp. nov., producing the antibiotic metabolites melinacidin Iv and chetracin B - Ghada A Ebead; David P. Overy; Fabrice Berrué; Russell G. Kerr (IMA Fungus)
Westerdykella reniformis Ebead & Overy sp. nov. is described based on morphology and phylogenetic analyses using ITS, nLSU rDNA, and β-tubulin gene sequences. Westerdykella reniformis is characterized by the production of cleistothecioid ascomata, containing small globose to subglobose asci with 32, aseptate, dark colored, pronouncedly reniform ascospores having a concave central groove. The isolate was obtained from a red alga (Polysiphonia sp.) collected from the tidal zone in Canada at low tide. Organic extracts enriched in extrolites, obtained from fermentation on a rice-based media, inhibited the growth of methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus faecium (VRE), S. warneri, and Proteus vulgaris. Presented here is the identification of the compounds responsible for the observed antimicrobial activity, the taxonomic description of W. reniformis, and a dichotomous key to the known species of Westerdykella based on macro- and micromorphological characters.